KETERJANGKAUAN PETANI TERHADAP SUMBER INFORMASI ( Studi Pada Anggota Kelompok Petani Pemakai Air (Kp2a) Di Kecamatan Seginim Kabupaten Bengkulu Selatan ) - Purwoko, Agus; Yuliarso, M. Zulkarnain; Weldyansyah, . (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2007)
The object of this research was to identify about the exposure to sources information in water user farmer member group (KP2A), to know relation characteristic farmers group in (KP2A) with sources of information and to know model and communication network in farmers member group of (KP2A) at Seginim District in South Bengkulu Regency. This research was conducted on 5 – 15 Desember 2006 at Seginim District. The research method use multistage random sampling for 60 members of farmers group. Result of this research indicated that five factors of the farmers such at formal education, income, experient in KP2A, motivation of work and perception to information related for the exposure to sourch of information there are on the middle category. The result of study indicated that ekxstention activity conducted with interactive models and all-channels comonity networking.